Storm Surge Generation by Winter Cyclones at Alexandria, Egypt - Hamed, A. A.; El Gindy, A. A. (The International Hydrographic Review, 2015)
The storm surges generated by winter cyclones in the Eastern Mediterranean, at Alexandria coast, are classified according to the synoptic situations. The data used are the hourly sea level values in the western harbour of Alexandria, the atmospheric pressure and the wind velocity at a station nearby the tide gauge during storm periods, from 1971 to 1984. Five types of storm surges were identified. Type A represents the weak surge case with a maximum residual of the order of 12-18 cm. Type B has a maximum residual between 20 and 24 cm. Type C is a moderate surge with an average maximum residual (26-30 cm). Type D has a strong surge, between 35 and 38 cm. Finally, type E has the strongest surge, reaching 43 cm. The depression tracks associated with each type are presented and the observed surges are compared with calculated ones using an equation given by Hamed (1983). A reasonable agreement, with a standard deviation ± 5 cm, was found between observations and calculations.